Hybrid Value Creation: A systematic review of an evolving research area - Velamuri, Vivek; Neyer, Anne-Katrin; Möslein, Kathrin (Journal für Betriebswirtschaft, 2011)
This systematic review analyses literature on the work of hybrid value creation, i.e. the process of generating additional value by innovatively combining products (tangible component) and services (intangible component). A state of the art report on hybrid value creation is delivered by first systematically identifying and then analyzing 169 publications focusing on hybrid value creation. The identified publications are clustered into eight categories based on their links and interactions and thus a mapping of this evolving field is suggested. A discussion and reflection of the findings with respect to the pervasiveness of literature and the research methodologies used is provided. The paper concludes by identifying some dominant strategic gaps in the overall research landscape and provides directions for future research. © 2011 Wirtschaftsuniversität Wien, Austri
WiSo-Import:2015-03-26:547
Keywords: Innovation